Out of the ordinary : folklore and the supernatural - Walker, Barbara, 1946- (UPCC book collections on Project MUSE., 1995)
"This contributed volume explores the functions of belief and supernatural experience within an array of cultures, as well as the stance of academe toward the study of belief and the supernatural. The essays in this volume call into question the idea that supernatural experience is extraordinary."--Publisher's description